Variations in the patterns of prevalence and therapy in Australasian Parkinson's disease patients of different ethnicities. Issue 1 (23rd March 2020) - Alamri, Yassar; Pitcher, Toni; Anderson, Tim J
Abstract : Parkinson's disease (PD) is the second most common neurodegenerative disease in the elderly after Alzheimer's disease. It is expected that PD cumulative incidence will increase in the future, as there are far more people surviving into late age than there ever used to be. While most commonly idiopathic, rare forms of PD can be familial/genetic. In addition, socioeconomic, cultural and genetic factors may influence the way in which anti-parkinsonian medications are prescribed, and how patients respond to them. This review aims to highlight the potential impact of genetic variation on the epidemiology and therapeutics of PD, focusing on data from New Zealand and Australia.